THE EFFECTIVENESS OF CONSTRUCTION GOODS AND SERVICES PROCUREMENT LAWS ON PRIVATE CONTRACTORS: A LEGAL SYSTEM PERSPECTIVE LAWRENCE M. FRIEDMAN - Augustinus Setijanto; Tedi Sudrajat; Sami'an Sami'an (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Public procurement of construction works constitutes a strategic instrument for national development; however, in practice it continues to face complex legal problems. These problems do not merely arise from procedural violations or corrupt intent, but also from unclear administrative authority, regulatory complexity, and weak legal culture in procurement implementation. Such conditions have contributed to increasing procurement disputes and the risk of policy criminalization, particularly affecting private contractors who perform works based on administrative orders issued by authorized officials. This paper aims to analyze legal problems in construction procurement in Indonesia by applying Lawrence M. Friedman’s legal system theory, which emphasizes three interrelated elements: legal structure, legal substance, and legal culture. The research employs a normative legal method with statutory, conceptual, and case-based approaches, analyzed through qualitative-descriptive techniques based on procurement regulations, legal doctrines, and judicial decisions as well as procurement practices. The analysis demonstrates that the ineffectiveness of construction procurement law stems from an imbalance among the three elements of the legal system. Weak coordination within the enforcement structure leads to the criminalization of administrative errors, complex legal substance creates ambiguity and risky discretion, while a permissive legal culture exacerbates deviations in practice. This paper offers a systemic reform perspective by emphasizing clearer differentiation between administrative and criminal liability, stronger legal protection for good-faith private contractors, and the reinforcement of ethical values and legal culture in procurement governance. Through this approach, construction procurement law is expected to function more effectively in achieving legal certainty, justice, and utility for sustainable national development.